Investigating factors influencing patient trust in a developing Pacific Island Country, Fiji, 2018 - Chandra, Swastika (Heliyon, 2020)
INTRODUCTION: In spite of the current evidence on positive impacts of patient trust on health outcomes, there are limited studies carried out in Pacific Island countries. This qualitative study aimed to explore the factors associated with patient trust in their doctors in Fiji. MATERIALS AND METHODS: With use of grounded theory research design, twenty participants attending the outpatient department of the health centers in the Suva Sub-division, Fiji were recruited. Audio-recorded in-depth interview was conducted using a semi-structured questionnaire. Transcribed data were analyzed using manual thematic analysis. RESULT: This study showed that interpersonal skills, communication skills, overall attitude and approach (customer care), clinical skills, improving health literacy and patient centred care were some of the factors influencing the level of trust patients had in their doctors. Though, together with communication and explanation, performing physical examination seemed to be bigger influencer of patient trust. CONCLUSION: It can be concluded that developing policies to improve doctors' communication skills, clinical skills, patients’ health literacy and customer care in Fiji can lead to better patient trust in their doctors.